Challenges of implementing a climate-smart agriculture-based curriculum in agricultural vocational schools: evidence from Iran - Jomegi, Mehdi; Niknami, Mehrdad; Sabouri, Mohammad Sadegh; Bijani, Masoud (Frontiers in Sustainable Food Systems, 2024)
The research aimed to identify the challenges of developing and implementing a climate-smart agriculture (CSA)-based curriculum in Iran’s agricultural vocational schools. It was exploratory descriptive-analytical in nature and applied in goal, in which data were collected with the library and deep interview method. The research methodology was based on grounded theory. The statistical population was composed of 16 researchers, authors, managers, and experts of the Office of Textbook Compilation of the Organization for Educational Research and Planning and the Research Center of Educational Studies. The participants were selected by the homogenous purposive sampling method. The interview with the target population continued until it reached theoretical saturation. Data were analyzed using the content analysis method. The data collected in the interviews were subjected to open, axial, and selective coding, which resulted in deriving 119 concepts and 28 categories. The results revealed a seven-dimension structure composed of the challenges related to determining educational goals, trainees, trainers’ professional process, teaching methods, curriculum content selection and organization, curriculum implementation, and curriculum appraisal. The results can help the experts in the Office of Textbook Compilation experts adopt smarter policies and solutions to solve the challenges of developing and implementing a CSA-based curriculum in agricultural vocational schools in Iran.